RANCANG BANGUN DAN PENGUJIAN MESIN PENYANGRAI KACANG TANAH KAPASITAS 10 KG/PROSES - Melvin Emil Simanjuntak; Melvin Bismark H. Sitorus; Mhd. Daud Pinem; Syariful Hikmah Sormin; Penteris Rumisar P Nabaho; Henry Hasian Lumbantoruan (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
Currently, the process of roasting peanuts in the North Tapanuli Regency area is still done manually. This will result in fatigue for the operator. To improve this condition, a roasting machine is needed to facilitate the roasting process. The peanut roaster machine that was designed in this study has a roasting tube as the main component with an electric motor as the prime mover. In addition there is a shaft, gearbox stirrer and clutch. The results of this design obtained power of prime mover and tube rotation of 1/2 hp and 28 rpm. The machine use a ceramic gas stove as heater. The experimental results show the machine can operate properly. The time needed to roast 10 kg of peanuts is 1 hour. BEP units obtained as much as 810 kg. The maintenance is carried out by cleaning and providing lubricant especially on the gearbox.